2022
DOI: 10.1038/s42004-022-00635-1
|View full text |Cite
|
Sign up to set email alerts
|

Acid anion electrolyte effects on platinum for oxygen and hydrogen electrocatalysis

Abstract: Platinum is an important material with applications in oxygen and hydrogen electrocatalysis. To better understand how its activity can be modulated through electrolyte effects in the double layer microenvironment, herein we investigate the effects of different acid anions on platinum for the oxygen reduction/evolution reaction (ORR/OER) and hydrogen evolution/oxidation reaction (HER/HOR) in pH 1 electrolytes. Experimentally, we see the ORR activity trend of HClO4 > HNO3 > H2SO4, and the OER activity tren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
60
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 103 publications
(216 reference statements)
8
60
0
Order By: Relevance
“…[16,39] Thus, when too many oxyanions are present, they will block the OER active sites. [23,40,41] This competition is consistent with the observation that the addition of oxyanions to the electrolyte first leads to an improvement of the OER activity (see following paragraphs), but after a certain concentration (in the order of magnitude of 0.1 M) the overpotential increases. [15,16] In this regard, it is worth mentioning that anodic potentials can increase the local concentration of (oxy)anions in the (near-)surface area of the electrode, as oxyanion migration into the double-layer can take place to compensate the build-up positive charge on the electrode surface.…”
Section: àsupporting
confidence: 88%
See 1 more Smart Citation
“…[16,39] Thus, when too many oxyanions are present, they will block the OER active sites. [23,40,41] This competition is consistent with the observation that the addition of oxyanions to the electrolyte first leads to an improvement of the OER activity (see following paragraphs), but after a certain concentration (in the order of magnitude of 0.1 M) the overpotential increases. [15,16] In this regard, it is worth mentioning that anodic potentials can increase the local concentration of (oxy)anions in the (near-)surface area of the electrode, as oxyanion migration into the double-layer can take place to compensate the build-up positive charge on the electrode surface.…”
Section: àsupporting
confidence: 88%
“…Density functional theory (DFT) calculations revealed that the adsorption energy is often negative (e.g., −1.9 eV for SeO 4 2− on NiOOH) [15] and occurs at the same transition metal sites where the OER intermediates are adsorbed (Ni preferred to Fe) [16, 39] . Thus, when too many oxyanions are present, they will block the OER active sites [23, 40, 41] . This competition is consistent with the observation that the addition of oxyanions to the electrolyte first leads to an improvement of the OER activity (see following paragraphs), but after a certain concentration (in the order of magnitude of 0.1 M) the overpotential increases [15, 16] .…”
Section: The Effect Of Surface‐adsorbed Oxyanionssupporting
confidence: 73%
“…An increase in the H 2 SO 4 electrolyte concentration suppressed the electrodeposition of the [Ag + Bi]­O x catalyst as concluded from the more positive onset potential on the RHE scale and lower reductive stripping peak in voltammetry (Figure S11). It is also noted that increased concentrations of the H 2 SO 4 electrolyte were reported to suppress the OER kinetics due to specific surface adsorption. , Most importantly, the stability of the electrodeposited [Ag + Bi]­O x system was not affected by pH in any significant way within the examined range, as the catalytic material was able to form and remain stable for extended durations in both the presence and absence of metal precursors in the electrolyte solutions.…”
Section: Resultsmentioning
confidence: 92%
“…It is also noted that increased concentrations of the H 2 SO 4 electrolyte were reported to suppress the OER kinetics due to specific surface adsorption. 63,64 Most importantly, the stability of the electrodeposited [Ag + Bi]O x system was not affected by pH in any significant way within the examined range, as the catalytic material was able to form and remain stable for extended durations in both the presence and absence of metal precursors in the electrolyte solutions.…”
Section: −2mentioning
confidence: 99%
“…The majority of recent studies have been carried out in perchloric acid electrolytes, as the adsorption of perchlorate anions is negligible compared to that of strongly adsorbing anions from other electrolytes such as sulfuric or phosphoric acid. 40,41 In particular, the anions from sulfuric and phosphoric acid electrolytes typically act as poisoning 'spectator' species for the ORR, as they block Pt active sites for this reaction. 40,[42][43][44][45] In particular, works by Adzic and Markovic 46 and Arenz 47,48 and their respective coworkers have elucidated distinct mechanisms in which anions from H 3 PO 4 (and H 2 SO 4 ) electrolytes block the Pt surface, as illustrated in Figure 1, thereby hindering ORR to proceed.…”
Section: Introductionmentioning
confidence: 99%